An agricultural application of homœopathy - Kayne, Steven (British Homeopathic Journal, 1991)
A field trial in which four homœopathic sprays were applied to rye grass is reported. The aim of the trial was to determine whether any significant effect on growth could be achieved when compared with similar applications of nitrogen fertilizer, and a control. At the particular dosages and strengths chosen no such effect was perceived; however a method for testing homœopathic sprays were established. The results are presented and analyzed. Suggestions are made for further work.
Keywords: Agriculture; Field trial; Controlled trial; Plant growth; Homœopathic spray; Steiner